Laparoscopic resection of a paraganglioma located on the border of the thoracic and abdominal cavities using a transabdominal‐transdiaphragmatic approach. Issue 2 (May 2015) - Sunose, Yutaka; Hirai, Keitaro; Nakazawa, Seshiru; Yoshinari, Daisuke; Ogawa, Hiroomi; Tsukagoshi, Hiroshi; Takahashi, Norifumi; Yamazaki, Hodaka; Motegi, Yoko; Miyamae, Yohei; Igarashi, Takamichi; Takahashi, Kengo; et al.
Abstract: We treated a 64‐year‐old woman with high blood pressure. Catecholamine metabolite levels were elevated in the blood and urine. CT revealed a densely stained tumor on the right side of the descending aorta dorsal to the inferior vena cava. PET‐CT revealed abnormal accumulation of 18 F‐fluorodeoxyglucose, and 123 I‐meta‐iodo‐benzylguanidine uptake was apparent on scintigraphy. The tumor was determined to be a paraganglioma located on the border between the thoracic and abdominal cavities, and laparoscopic tumorectomy was performed. The patient was placed in the left lateral position. The right lobe of the liver was turned over, and we cut the diaphragm to expose the front of the tumor. We resected the straight artery flowing in from the aorta and removed the tumor safely. Herein, we describe the removal of a paravertebral paraganglioma located in the border of the thoracic and abdominal cavities with a laparoscopic transabdominal‐transdiaphragmatic approach.